Perbarengan Tindak Pidana Menurut Hukum Pidana Islam (Analisis Putusan Hakim Nomor 39/Pid.B/2019/Pn.Tdn) - Muhammad Maulana; Edi Yuhermansyah; Sumita Dewi (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2022)
Concurrent criminal acts often occur in the community, even in the process many have been resolved in court, one of these cases is the Tanjungpandan District Court Decision Number 39/Pid.B/2019/PN.Tdn. In this decision, the perpetrator was charged with committing a crime concurrently between premeditated murder and theft in aggravating conditions. In this paper, the main issue raised is about how the judge's considerations in imposing sentences on the perpetrators and the review of Islamic criminal law against the concurrent criminal acts in the decision. This paper is presented with a literature study, with the type of normative legal research (juridical-normative). This paper concludes that the reasons and considerations of the judge in sentencing the perpetrators of the crime of premeditated murder and theft in Decision Number 39/Pid.B/2019/PN.Tdn include two criteria, namely the case of premeditated murder through Article 340 of the Criminal Code. In the review of Islamic criminal law, the concurrent crime of murder and theft is included in the theory of al-jabb, namely a punishment that can absorb other punishments, namely the death penalty.